WAYS OF DEVELOPMENT OF ALGORITHMIC LITERAC - Astambaeva, Ж.Қ; Zhumabaeva, А.Е (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In the modern era of Cybernetics, future primary school teachers should use the algorithms they use in everyday life creatively in the educational process. When performing various exercises that are considered in elementary school math lessons, the future specialist must use explicit algorithms himself and correctly implement them when teaching students. In primary school mathematics, future teachers use implicit algorithms such as: an algorithm for solving various types of problems, algorithms for solving complex equations and expressions, an algorithm for constructing certain geometric shapes, an algorithm for using the Union and intersection of sets in solving problems, and an algorithm for performing tasks related to simple and geometric quantities. The article discusses the method of applying these algorithms and the ways of developing algorithmic literacy of future specialists.